Diet and the risk of head-and-neck cancer among never-smokers and smokers in a Chinese population. (February 2017) - Butler, Carrie; Lee, Yuan-Chin Amy; Li, Shuang; Li, Qian; Chen, Chien-Jen; Hsu, Wan-Lun; Lou, Pen-Jen; Zhu, Cairong; Pan, Jian; Shen, Hongbing; Ma, Hongxia; Cai, Lin; et al.
Highlights: Risk of HNC increases with more frequent consumption of processed meat and fermented foods. Risk of HNC decreases with frequent consumption of fruits and vegetables. Protective ORs were observed for higher egg consumption among never-smokers. Abstract: Background: Few studies have been conducted in China to investigate the association between diet and the risk of head-and-neck cancer (HNC). The aim of this study was to determine the relationship between diet and HNC risk in the Chinese population and to examine whether smoking status has any effect on the risk. Methods: Our multicenter case–control study included 921 HNC cases and 806 controls. We obtained information on the frequency of both animal- and plant-based food consumption. Unconditional logistic regression was used to estimate the odds ratios (ORs) and 95% confidence intervals (95%CIs). Results: The risk of HNC increased with more frequent consumption of processed meat and fermented foods but decreased with frequent consumption of fruits and vegetables. There was a significant increasing P for trend of 0.006 among smokers who consumed meat and an increased OR among smokers who consumed processed meat (OR 2.95, 95%CI 1.12–7.75). Protective odds ratios for vegetable consumption were observed among smokers only. We also observed protective odds ratios for higher egg consumption among never-smokers ( P for trend = 0.0.003). Conclusions: Reduced HNC risks were observed for high fruit and vegetable intake, a finding consistent with the results of previous studies. Processed meat intake was associated with an increased risk. The role of dietary factors in HNC in the East Asian population is similar to that in European populations.